The absorption kinetics of Antarctic krill oil phospholipid liposome in blood and the digestive tract of healthy mice by single gavage - Lin Li; Chengcheng Wang; Shan Jiang; Rong Li; Tiantian Zhang; Changhu Xue; Teruyoshi Yanagita; Xiaoming Jiang; Yuming Wang (Food Science and Human Wellness)
Antarctic krill (Euphausia superba) oil has been gaining increasing attention due to its nutritional and functional potentials. Krill oil usually contains a high concentration (about 50%) of phospholipids (AKOP) rich in DHA and EPA accompanied with 30%–40% triacylglycerols. Phospholipids can be made into liposomes without emulsifiers due to its amphiphilic characteristics. However, the absorption kinetics of AKOP liposome in vivo is not clear, which restrict the molecular mechanism analysis related to its distinct bioactivities. The lipid analysis in serum, small intestinal content and wall was carried out after oral administration of AKOP liposome to illustrate its absorption kinetics in blood and the digestive tract of healthy mice by single gavage. The major type of the obtained AKOP was phosphatidylcholine, and the total contents of the DHA and EPA were 29.31%. AKOP liposome was almost completely digested in the small intestine in 1 h and the hydrolysis products could be quickly absorbed by intestinal enterocytes. The DHA in serum peaked at 2 h after administration of AKOP liposome. AKOP liposome could be quickly digested and absorbed in vivo. The obtained results might provide a scientific basis for the molecular mechanism analysis related to distinct bioactivities of Antarctic krill oil phospholipid. Keywords: Antarctic krill oil, Phospholipid, Liposome, Single gavage, Absorption kinetics